Lucuma (Pouteria lucuma): Composition, bioactive components, antioxidant activity, uses and beneficial properties for health - Maza-De la Quintana, Ricardo (2020)
Lucuma is a superfruit of Andean origin, with ovoid shape, greenish yellow color, nice smell, and intense sweet taste. In recent years this superfruit has won great popularity in the international market, and its demand tends to increase exponentially in the future, due to its properties as a functional food for its bioactive components like β-carotens, niacin, phenolic components, phytosterols, among others that give this fruit beneficial properties for health, such as its anti-inflammatory action, antioxidant effect, antihypertensive action, antibacterial, energizing, healing, and its use as a natural sweetener. Currently, research is being carried out about its influence on metabolism, its antidiabetic, anti-cancer capacity and its use to prevent heart disease and counteract Alzheimer's.  The properties of lucuma are still under study and greater benefits and applications are expected. The objective of this work was to announce the components and beneficial properties of lucuma known from the point of view of health.